Translator's Tyranny: A Critical Analysis of the Book Entitled “A Consideration of the Translation of Modern Political Thought's Texts: A Case Study of Machiavell's Prince “ - Shervin Moghimi; Yashar Jeirani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This paper is a review of Javad Tabatabee's book titled A Consideration of the Translation of Modern Political Thought' Texts: A Case Study of Machiavell's Prince. In this book, Tabatabaee argues that two main factors of unreliable translation in the field of political philosophy are translator's artistic playing with words and his lack of knowledge about current and important interpretations of major works of political philosophy. In this paper, we argue that Tabatabaee's claims are for the most part plausible. Nevertheless, it seems that Tabatabaee ignores another important factor responsible for unreliable translations, i.e., translator's alteration of literal translation of philosopher's text by virtue of his assurance that he has a sufficient understanding of philosopher's meaning. Therefore, we try to argue that even if we observe two main conditions of good translation mentioned by Tabatabaee, this will not necessarily lead to a reliable translation. Thus, in addition to Tabatabaee's two main conditions, the translator also must observe the literal approach in translating philosophical texts.